Influence of Onset to Imaging Time on Radiological Thrombus Characteristics in Acute Ischemic Stroke - Tolhuisen, Manon L.; Kappelhof, Manon; Dutra, Bruna G.; Jansen, Ivo G. H.; Guglielmi, Valeria; Dippel, Diederik W. J.; van Zwam, Wim H.; van Oostenbrugge, Robert J.; van der Lugt, Aad; Roos, Yvo B. W. E. M.; Majoie, Charles B. L. M.; Caan, Matthan W. A.; et al. (Frontiers in Neurology, 2021)
Introduction: Radiological thrombus characteristics are associated with patient outcomes and treatment success after acute ischemic stroke. These characteristics may undergo time-dependent changes due to factors influencing thrombus architecture like blood stasis, clot contraction, and natural thrombolysis. We investigated whether stroke onset-to-imaging time was associated with thrombus length, perviousness, and density in the MR CLEAN Registry population. Methods: We included 245 patients with M1-segment occlusions and thin-slice baseline CT imaging from the MR CLEAN Registry, a nation-wide multicenter registry of patients who underwent endovascular treatment for acute ischemic stroke within 6.5 hours of onset in the Netherlands. We used multivariable linear regression to investigate the effect of stroke onset-to-imaging time (per five minutes) on thrombus length (in mm), perviousness and density (both in Hounsfield Units). In the first model, we adjusted for age, sex, intravenous thrombolysis, antiplatelet use, and history of atrial fibrillation. In a second model, we additionally adjusted for observed versus non-observed stroke onset, CT-angiography collateral score, direct presentation at a thrombectomy-capable center versus transfer, and stroke etiology. We performed exploratory subgroup analyses for intravenous thrombolysis administration, observed versus non-observed stroke onset, direct presentation versus transfer, and stroke etiology. Results: Median stroke onset-to-imaging time was 83 (interquartile range 53-141) minutes. Onset to imaging time was not associated with thrombus length nor perviousness (β 0.002; 95% CI -0.004 to 0.007 and β -0.002; 95% CI -0.015 to 0.011 per five minutes, respectively) and was weakly associated with thrombus density in the fully adjusted model (adjusted β 0.100; 95% CI 0.005 to 0.196 HU per five minutes). The subgroup analyses showed no heterogeneity of these findings in any of the subgroups, except for a significantly positive relation between onset-to-imaging time and thrombus density in patients transferred from a primary stroke center (adjusted β 0.18; 95%CI 0.022-0.35). Conclusion: In our population of acute ischemic stroke patients, we found no clear association between onset-to-imaging time and radiological thrombus characteristics. This suggests that elapsed time from stroke onset plays a limited role in the interpretation of radiological thrombus characteristics and their effect on treatment results, at least in the early time window.